Climate Smart Agriculture Building Resilience to Climate Change - Lipper, Leslie; McCarthy, Nancy; Zilberman, David; Asfaw, Solomon; Branca, Giacomo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is open access under a CC BY-NC-SA 3.0 IGO license.
Chapter 1: Introduction -- Chapter 2: A Short History of the Evolution of the Climate Smart Agriculture Approach and its Links to Climate Change and Sustainable Agriculture Debates -- Chapter 3:Economics of Climate-Smart Agriculture -- Chapter 4: Innovation in Response to Climate Change -- Chapter 5: Use of Satellite Information on Wetness and Temperature for Decision of Crop Yield Prediction, River Discharge and Planning -- Chapter 6: Early Warning Techniques for Local Climate Resilience: Smallholder Rice in Lao PDE -- Chapter 7 : Farmers' Perceptions of and Adaptations to Climate Change in Southeast Asia: The Case Study from Thailand and Vietnam -- Chapter 8: U.S. Maize Yield Growth and Countervailing Climate Change Impacts -- Chapter 9: Understanding Tradeoffs in the Context of Farm-Scale Impacts: An Application of Decision-Support Tools for Assessing Climate Smart Argiculture -- Chapter 10: Can Insurance Help Manage Climate Risk and FoodInsecurity?: Evidence from the Pastoral Regions of East Africa -- Chapter 11: Can Cash Transfer Programs Promote Household Resilience?: Cross-Country Evidence from Sub-Saharan Africa -- Chapter 12: Input Subsidy Programs and Climate Smart Agriculture -- Chapter 13: Robust Decision Making for a Climate-Resilient Development of the Agricultural Sector in Nigeria -- Chapter 14: Using AgMIP Regional Integrated Assessment Methods to Evaluate Vulnerability, Resilience and Adaptive Capacity for Climate Smart Agricultural Systems -- Chapter 15: Climate Smart Food Supply Chains in Developing Countries in an Era of Rapid Dual Change in Agrifood Systems and the Climate -- Chapter 16: The Adoption of Climate Smart Agriculture: The Role of Information and Insurance under Climate Change -- Chapter 17: A Qualitative Evaluation of CSA Options in Mixed Crop-Livestock Systems in Developing Countries -- Chapter 18: Identifying Strategies to Enhance the Resilience of Smallholder Farming Systems: Evidence of Zambia -- Chapter 19: Climate Risk Management Through Sustainable Land and Water Management in Sub-Saharan Africa -- Chapter 20: Improving the Resilience of Central Asian Agriculture to Weather Viability and Climate Change -- Chapter 21: Managing Environmental Risk in the Presence of Climate Change: The Role of Adaption in the Mile Basin of Ethiopia -- Chapter 22: Diversification as Part of a CSA Strategy: The Cases of Zambia and Malawi -- Chapter 23: Economic Analysis of Improved Smallholder Paddy and Maize Production in Northern Vietnam and Implications for Climate-Smart Agriculture -- Chapter 24: Synthesis: Devising Effective Strategies and Policies for CSA -- Chapter 25: Conclusions and Policy Implications.
Keywords: Agriculture -- Economic aspects; Economic development; Economic policy; Agricultural Economics; Economic Development, Innovation and Growth; Economic Policy